2017
DOI: 10.4018/ijskd.2017100103
|View full text |Cite
|
Sign up to set email alerts
|

From Human-Centered Design to Disabled User & Ecosystem Centered Design in Case of Assistive Interactive Systems

Abstract: This article aims to revisit and to adapt the Norman's theory of action by focusing on the design of interactive systems for disabled people. The background section demonstrates that there is a need to include all the stakeholders involved in the environment of the disabled person in the design process, constituting his or her ecosystem. Then the adaptation of the Norman's theory action, considering explicitly the ecosystem is justified; examples of the both role of the disabled people and members of his/her e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0
10

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
1

Relationship

4
1

Authors

Journals

citations
Cited by 33 publications
(25 citation statements)
references
References 23 publications
0
15
0
10
Order By: Relevance
“…Since the persons with ASD cannot express their needs and the context use due to communication and behavior disorder, family and professional caregivers [7] are involved in the UCD. Guffroy et al [8] suggested involving the family, professional and human environments that are part of his or her ecosystem. One approach is to integrate this ecosystem into the user-centered design method.…”
Section: The User-centered Design Implemented For Asdmentioning
confidence: 99%
“…Since the persons with ASD cannot express their needs and the context use due to communication and behavior disorder, family and professional caregivers [7] are involved in the UCD. Guffroy et al [8] suggested involving the family, professional and human environments that are part of his or her ecosystem. One approach is to integrate this ecosystem into the user-centered design method.…”
Section: The User-centered Design Implemented For Asdmentioning
confidence: 99%
“…9241 [2]. Guffroy et al [3] have introduced the "ecosystem" as the social environment involved in the design of assistive technologies. This ecosystem is made up of family and/or professional careers, friends, and colleagues in relation to his or her professional activity, who are involved in the activities of the person with a disability.…”
Section: Introductionmentioning
confidence: 99%
“…This ecosystem is made up of family and/or professional careers, friends, and colleagues in relation to his or her professional activity, who are involved in the activities of the person with a disability. For people with communication impairments (little or no written and oral language), the participation of ecosystem members is essential in order to design assistive technologies that takes into account the context of use and the expression of needs, see Guffroy et al [3], Derboven et al [4]. In addition, these disabled persons need assistive technologies to communicate with their caregivers and their family.…”
Section: Introductionmentioning
confidence: 99%
“…Plusieurs travaux de recherche ont proposé des adaptations de la mis en oeuvre la méthode de la CCU. Les travaux [14], [3], [4] et [6] ont montré que la participation de personnes (famille, personnels du médico-social, etc.) proches des utilisateurs était bénéfique pour concevoir des prototypes répondant à leurs besoins.…”
Section: Introductionunclassified